2000
DOI: 10.1159/000039757
|View full text |Cite
|
Sign up to set email alerts
|

Influence of α-Thalassemia Trait on the Prevalence and Severity of Anemia in Pregnancy among Women in Kuwait

Abstract: α-Thalassemia is very common in the Kuwaiti population, but its influence on anemia of pregnancy has not been previously investigated. We have screened a group of 59 anemic (Hb <11 g/dl) pregnant women for the α-thal-2 (–α-3.7 kb) deletion which is the commonest α-thal allele in this community, using a polymerase chain reaction method. A control group of 35 nonanemic (Hb ≥11 g/dl) pregnant women was studied for comparison. All the women were in the second or third trimester of pregnancy. Among the 94 women in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Malaria and hookworm infections are not endemic in Kuwait due to improved (Hira et al 1988, Iqbal et al 1999). However, studies have shown that a-thalassemia is common in the Kuwaiti population (Diejomaoh et al 2000). In the present study we do not have any information on hemoglobinopathies, and this merits further investigations.…”
Section: Discussionmentioning
confidence: 60%
“…Malaria and hookworm infections are not endemic in Kuwait due to improved (Hira et al 1988, Iqbal et al 1999). However, studies have shown that a-thalassemia is common in the Kuwaiti population (Diejomaoh et al 2000). In the present study we do not have any information on hemoglobinopathies, and this merits further investigations.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies of anemia in Kuwait have focused on hemoglobinapathies such as sickle cell disease or α- or β-thalassemia [ 7 , 6 , 26 ]. Studies of nutritional causes of anemia and ID in Kuwait are based on small non-representative samples taken from clinical or hospital-based studies [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of anemia in Kuwait have focused on the genetic causes of anemia such as sickle cell disease or thalassemia [ 6 , 7 ]. Estimates of nutritional causes of anemia have been based on small epidemiological studies, or clinical, or hospital-based studies [ 8 , 9 , 10 ] with limited generality.…”
Section: Introductionmentioning
confidence: 99%
“…1 % in Baghdad (502) (Yahya et al 1996) 4.14 % in Sulaimania, northeast Iraq (1,472) (Jalal et al 2008) Jordan 3.04 % (1,020) (Babiker et al 1999) 2.26 % in Badia region (1,020) (Babiker et al 1999) 5.93 % (2,858) (Sunna et al 1996) 3.1 % in North Jordan (1,000) (Bashir et al 1992) 3.5 % (1,000) (Bashir et al 1992) 3.5 % in Jordan valley (456) (Bashir et al 1991) 3.3 % (456) (Bashir et al 1991) Kuwait 3 % (Galanello et al 2003) 26.5 % (94) (Diejomaoh et al 2000) 4.6 % (345) (Simsek et al 1993 (Rajab et al 2000) 38.9 %. (White et al 1986) 1.5 % (1,000) (White et al 1993) 48.5 % (7,837) (Alkindi et al 2010) 2.8 % (7,837) (Alkindi et al 2010) 58.3 % (87) (Hassan et al 2010) 2.4 % (790) (White et al 1986) Palestinian territories 4.3 % (1,650) (Sirdah et al 1998) 3.5 % in West Bank (Darwish et al 2005).…”
Section: Introductionmentioning
confidence: 99%